ANALISIS TINGKAT KEPATUHAN TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS DI PUSKESMAS TEMINDUNG - Paranael, Paranael; Geografi, Liniati; Simanullang, Raymon (Jurnal Farmasi Etam (JFE), 2024)
The Central Statistics Agency of East Kalimantan Province recorded 337 HIV/AIDS cases in 2023, with Samarinda accounting for the highest number of cases (134). Effective HIV/AIDS treatment is key to slowing disease progression, improving patients' quality of life, and reducing the risk of viral transmission. Antiretroviral therapy (ARV) has become the standard of care for HIV/AIDS patients. This study aims to analyze adherence to antiretroviral therapy in HIV/AIDS patients at the Temindung Community Health Center. The method used was a quantitative cross-sectional approach, where the independent and dependent variables were measured at a single point in time. Data were collected through observation, questionnaires, data collection techniques, and the number of HIV/AIDS patient visits to the Temindung Community Health Center Pharmacy Unit. The expected outcomes of this study are improved patient understanding and adherence to antiretroviral therapy (ARV), as well as identification of factors influencing adherence levels in HIV/AIDS patients at the Temindung Community Health Center. Based on the analysis of data obtained through observations, questionnaires, and the number of patient visits for ARV treatment, this study is expected to provide relevant recommendations to improve the quality of service and support the effectiveness of HIV/AIDS patient treatment at the Temindung Community Health Center.